Fiddler crabs and their above-ground sedimentary structures: a review - Pardo, Juan C. F. [UNESP]; Stefanelli-Silva, Gabriel; Christy, John H.; Costa, Tânia M. [UNESP] (Springer Nature, 2020)
Fiddler crabs are abundant, semi-terrestrial crustaceans inhabiting tropical, subtropical and warm temperate coasts worldwide. Some species build above-ground sedimentary structures at or near the opening to their burrows. The functions and shapes of these constructions vary interspecifically and according to the sex of the builder. Here, we compile the dispersed reports on these structures, suggest uniform naming for different shapes, review explanations for their functions and explore associations between the attributes of builders and their structures. We found that 47 fiddler crab species build at least one type (or subtype) of structure, including chimneys, hoods, pillars, semidomes, mudballs, and rims. Sedimentary structures show a strong association with sediment type as well as builder front type, genus and sex, but not with fiddler crab clade. Experimental studies have revealed distinct, sometimes multiple functions for some of these structures (e.g., female attraction, reduction of aggressive behavior and/or landmark orientation); however, most studies have been observational leaving the proposed functions of these structures for many species untested. Both field and laboratory experiments as well as observational studies can help us to better understand these sedimentary structures and their role in fiddler crab behavior and ecology.
Keywords: Burrow; Chimney; External structures; Hood; Mudball; Pillar; Rim; Semidome